CULTURAL CAPITAL AND FINANCIAL AWARENESS: ANALYZING STUDENT ENTREPRENEURIAL ASPIRATIONS IN ISLAMIC FINANCE - Furqan, Muhammad; Khairisma (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2023)
This comprehensive research focuses on the complex relationships between entrepreneurial goals among Malikussaleh University business and economics students. This study investigates how Sharia financial literacy and parents' socioeconomic status impact entrepreneurial interest. The research uses primary data collected from a sample of 110 respondents through the distribution of questionnaires. The data was analysed using a multiple linear regression model to produce findings. The study results reveal a positive correlation: parents' socioeconomic status and Sharia financial literacy substantially impact the entrepreneurial motivation of Malikussaleh University students studying business and economics. This suggests that students who are more educated in Sharia financial principles and come from wealthier homes are more likely to be interested in starting their own businesses. These findings affect entrepreneurial education, policy, and academic stakeholders, especially in Islamic finance. Understanding the critical impact of parental socioeconomic status and Sharia financial literacy, educators and policymakers can design interventions to provide a supportive environment for students to pursue their entrepreneurial dreams.